Double versus Single Phototherapy in the Treatment of Neonatal Hyperbilirubinemia (Mediscope, 2025)
Background: Hyperbilirubinemia is a common problem in full-term newborns. Since the 1950s, phototherapy has been the choice of treatment for lowering bilirubin concentration in neonates.Objective: To compare the effectiveness of single and double phototherapy and increasing spectral irradiance for decreasing serum bilirubin levels in neonates with indirect hyperbilirubinemia.Methods: An open-label, randomized controlled trial was conducted at Ad-din Sakina Women's Medical College, Jashore, from June to December 2022. Subjects were divided into two groups: those who received single phototherapy (n=35) and those who received double phototherapy (n=35). We included term newborns with neonatal jaundice in the first week of life. Serum bilirubin and average spectral irradiation levels were measured at baseline and after 12 hours and 24 hours of phototherapy treatment.Results: The mean total bilirubin levels of the single and double phototherapy groups at the beginning of therapy were 17.6±1.41 mg/dL and 17.5±1.32 mg/dL, respectively, with no significant difference between values. During the study period, the sum of average spectral irradiance by double phototherapy was significantly higher than that of single phototherapy (P < 0.05). A significantly greater decrease in bilirubin levels was observed in the double phototherapy group at 12 hours and 24 hours of phototherapy compared to the single phototherapy group (P